2012
DOI: 10.1002/poc.2923
|View full text |Cite
|
Sign up to set email alerts
|

Substituent effect study on δc values of the bridge group carbons in disubstituted cinnamyl aniline series

Abstract: The 13C nuclear magnetic resonance (NMR) chemical shifts δc of bridge group carbons (C‐β, C‐α, and C═N) were measured in this work for a wide set of substituted cinnamyl anilines p‐XC6H4CH═CHCH═NC6H4Y‐p (X = NO2, Cl, H, Me, MeO, or NMe2; Y = NO2, CN, CO2Et, Cl, F, H, Me, MeO, or NMe2) and were used to study the substituent effect. In the study on 13C NMR chemical shifts of the titled compounds with single substituent changed, for every bridge carbon δc, the effect of cinnamyl substituent X is opposite to that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 20 publications
0
19
0
Order By: Relevance
“…In previous investigation results of aromatic Schiff base, the coefficients in front of a substituent in the C‐terminal benzene ring are opposite to those in front of the substituent in the N‐terminal benzene ring. However, the coefficients in front of inductive effect parameters and conjugative effect parameters are positive in Eqn , which seems to be in conflict with the previous results.…”
Section: Resultsmentioning
confidence: 78%
See 3 more Smart Citations
“…In previous investigation results of aromatic Schiff base, the coefficients in front of a substituent in the C‐terminal benzene ring are opposite to those in front of the substituent in the N‐terminal benzene ring. However, the coefficients in front of inductive effect parameters and conjugative effect parameters are positive in Eqn , which seems to be in conflict with the previous results.…”
Section: Resultsmentioning
confidence: 78%
“…Although the correlation result of Eqn is good, there is a large standard deviation. In many previous types of work, it is confirmed that there is an interaction between substituents, and it cannot be ignored. In the investigation of δ C values for p ‐XCAY‐ p , the substituent interaction item, Δ σ 2 was recommended to be divided into two parts: normalΔσF*2 and normalΔσR*2.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is known that the length of the conjugated chain can affect the inductive and resonance effects and thus might lead to changes in the electron distribution. Cao et al [18] also investigated the substituent effects in M2 (Scheme 1). Our observations of the substituent effects in M2 encouraged us to prepare other type of benzylidene anilines, in which the conjugated chain in the aniline unit is elongated.…”
Section: Introductionmentioning
confidence: 99%